ANALISIS PENGGUNAAN BATERAI LITHIUM-ION SEBAGAI BATTERY BANK PADA STASIUN PENGISIAN SEPEDA LISTRIK - Pratomo, Setyo Fajar; Maulana, Eka; Dhofir, Moch. (Jurnal Mahasiswa TEUB, 2024)
Lithium-ion is a battery with high-density energy and a lower self-discharge. Moreover, lithium-ion batteries have no memory effect. One of the most used lithium-ion cells is lithium-ion 18650. The Tesla electric cars (model S and X) produced in 2013-2017 consist of a total of 8,256 Panasonic NCR18650B cells which capable to store 100 kWh of power, enabled people to drive up to 482km. Apart from the excellence, the increasing use of lithium-ion batteries in electric vehicles and electronic devices will create a lot of waste when the lithium-ion batteries used are worn out. Hence, this study aims to examine the feasibility of used lithium-ion batteries and reuse them as energy storage at electric bike charging stations in parking lot. The system is designed with a 275WP solar panel to charge the bank battery through the PWM solar charge controller, followed by charging an electric bike battery with the inverter. The battery bank is constructed by 30 cells of 18650 lithium-ion batteries which have already gone through an voltage, capacity, and internal resistance sorting process. The configuration used is the 6 series 5 parallel with charge capacity of each cell is on 2091 – 2366 mAh, resulting in saved energy as much as 243 Wh. The experimental results prove that the designed battery bank can fulfill its function as energy storage in the solar panel system. The time required to charge the bank battery fromempty to full is five hours. Besides, the battery bank is able to provide power through an inverter in order to charge an electric bike battery using a 25.2V 2A adapter. Keywords: 18650 Battery, Electric Vehicle, Lithium-ion, Solar Panel, Charging Station.